STUDENTS’ SPEAKING ANXIETY IN SPEAKING SKILLS IN THE CLASSROOM AS A FOREIGN LANGUAGE FOR THE 2nd GRADE AT SMA NEGERI 1 PAREPARE - Sudarmanto, Sudarmanto; Patahuddin, Patahuddin; Lestari, Putri Veronica (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
To speak English, someone, especially among students, needs to master several verbs, and one of the obstacles to speaking English is the lack of verbs among students. Therefore, students face various obstacles. Anxiety is one of the biggest obstacles for students. Therefore, the purpose of this research is to find out what is students' anxiety and what factors cause students' anxiety when speaking in English in class. The sample of this study was MIPA 5 students of XI class of SMAN 1 Parepare which consisted of 35 students. The approach used in this study is descriptive research and qualitative. This study uses two research instruments namely Horowitz et al. (1986) used the Foreign Language Classroom Anxiety Scale (FLCAS) and interviews. The questionnaire had 33 items consisting of 9 positive and 24 negative statements on a Likert scale of 1-5 points, while the interview consisted of 10 questions. According to the survey's findings, there was only 1 respondent with a "Very Anxious" anxiety level or 3%, 5 respondents had "Anxious" anxiety levels or 14%, 6 respondents had "Mildly Anxious" anxiety levels or 46%, 13 respondents had "Relaxed" anxiety levels or 37%, and there were no students with a "Very Relaxed" anxiety level. Considering this, it can be said that the students in Class XI MIPA 5 SMAN 1 Parepare are generally "Mildly Anxious" when speaking English in class. According to the results of the interviews, it is clear that some students who are learning English in a classroom setting still experience anxiety. The factors contributing to this include a lack of vocabulary, imprecise pronunciation, a lack of confidence, being unprepared if the teacher calls on a student to speak in English without warning, and a lack of motivation on the part of the students. From 35 students in class XI MIPA 5, the researchers only interviewed 14 sources.